Do microbes affect athletic performance? - Makin, S. (Nature, 2021)
A week before the 2015 Boston Marathon, Jonathan Scheiman, then a postdoctoral researcher in the lab of geneticist George Church at Harvard Medical School in Boston, Massachusetts, was racing around the city in a hire car collecting faeces. He gathered stool samples from runners planning to participate, as well as those from non-runners — mostly fellow postdocs. After the race, he revisited his donors to collect more samples. Four years later, his efforts were rewarded with a paper describing one of the first attempts to establish a causal link between the symbiotic community of microorganisms living in our guts and athletic performance. Although the gut microbiome has been implicated in numerous aspects of health and disease, links with athleticism are much less studied. Interest is growing, however, helped by advances over the past decade that enable researchers to reveal not just which microbes the gut harbours but also what they do. Such work suggests that the enormous diversity of organisms that make up a person`s gut microbiome — each as unique as a fingerprint — might converge on a smaller number of functions, which, in turn, could suggest candidate mechanisms. And although elite athletes and their coaches might hope to be the first to benefit, a deeper understanding of the link between the gut microbiome and physical fitness might instead benefit the health of the wider population.